IMPLEMENTASI METODE STORYTELLING UNTUK MENINGKATKAN KEMAMPUAN BAHASA ANAK - Muhammad Rizal Zaenulloh; Arif Ahmad Fauzi; Aan Rohaeni (Jurnal Pendidikan Islam dan Manajemen Ekonomi, 2025)
Language skills are an important aspect in early childhood development because they are the basis for communication and thinking. This study aims to determine the implementation of the storytelling method in improving the language skills of group B children at RA Tarbiyatusshibyan Cikondang Bojongpicung Cianjur. This study uses a quantitative approach with a pre-experimental method with a one-group pre-test and post-test design. The research subjects were 20 children aged 5–6 years. Data collection techniques were carried out through observation, testing, and documentation. The results of the Wilcoxon test showed a significance value of 0.000 (<0.05), which means there is a significant difference in children's language skills before and after the implementation of the storytelling method. Thus, the storytelling method is effective in improving the language skills of early childhood.